In Vitro Susceptibility of Haemophilus influenzae to Sulfamethoxazole-Trimethoprim and Cefaclor, Cephalexin, and Cephradine - Sinai, R. (1978)
Sulfamethoxazole-trimethoprim and three oral cephalosporins, cefaclor, cephalexin, and cephradine, were evaluated in vitro as possible alternatives to chloramphenicol in the treatment of non-central nervous system infections due to ampicillin-resistant Haemophilus influenzae. Sixty-four isolates of H. influenzae, including 31 β-lactamase-positive strains, were tested by the agar dilution method. All strains were inhibited by 0.78/0.039 μg sulfamethoxazole-trimethoprim per ml and by 0.78 μg of chloramphenicol per ml. At 6.25 μg/ml, 100, 11, and 3% of all strains were inhibited by cefaclor, cephalexin, and cephradine, respectively. Thus, on the basis of drug concentrations presumably achievable in serum, 100% of strains were susceptible to sulfamethoxazole-trimethoprim, chloramphenicol, and cefaclor. However, a considerable inoculum effect was noted with both β-lactamase-positive and -negative strains, when tested with sulfamethoxazole-trimethoprim; the minimal inhibitory concentrations of cefaclor were only slightly affected. Also, synergistic effects of sulfamethoxazole-trimethoprim, sulfamethoxazole-erythromycin, and sulfamethoxazole-cefaclor were seen when combinations were tested against both β-lactamase-positive and -negative strains, as determined by minimal inhibitory concentrations measured by the broth dilution method and by killing curve analyses. These results support further evaluation of these combinations and of cefaclor alone for the treatment of non-central nervous system infections due to H. influenzae.